The Mosaic Tradition - Victor Winnett, Frederick (Heritage, 2019)
For some two hundred years, Old Testament criticism has wrestled with the problem of the Hexateuch. The commonly accepted view is based on the Wellhausen Hypothesis, which has held saw over the mids of scholars, save for a conservative few, for nearly seventy years. According to the theory of Wellhausen, the Hexateuch is a combination of fource literary sources, J, E, D, and P, with numerous additions and retouchings by the symbols Rje, Rd and Rp. Professor Winnett's view is that the Books of Exodus and Numbers constitute one primary source, the Mosaic Tradition, which has been supplemented and rearranged by P. Dr. Winnett shows that shortly after the fall or the Northern Kingdom in 722 B.C. the Southern Kingdom under Hezekiah took advantage of the extinction of its rival to issue a revised version of the national tradition